PERSEPSI MASYARAKAT TERHADAP MITOS AIR MATAKIDI - La Ode Muhajirin Sahida; La Janu (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2018)
This study aims to reveal the perception of the public about the myth of Matakidi water in Matakidi Village, Lawa District, Muna Regency. In addition, it also aims to find out the influence of the myth on the community. This study uses Herbert Blummer's symbolic interactionism theory. Data collection is done through observation techniques, and interviews. The data collection is descriptive qualitative analysis. The results of this study indicate that there are several perceptions of the Matakidi Village community towards Matakidi water sources, including (1) matakidi water as a place to take drinking water; (2) natural water as a tourist place, because it is supported by its natural beauty; (3) matakidi water as a sacred or sacred place; (4) matakidi water as a means of mutual acquaintance-to recognize or intensify social solidarity. Keywords: community perceptions, myth, matakidi water.